Therapeutic Mandibular Incisor Extraction in Orthodontics: An Overview (Journal of Orofacial Research, 2024)
Therapeutic extraction of a mandibular incisor is an infrequent and possibly underused treatment strategy in Orthodontics. In carefully selected cases, the treatment outcomes are comparable and sometimes better than those with other extraction patterns. This article reviews all factors necessary for the diagnosis, treatment planning, and effective management of such cases.